Assessement of the progress made to give women access to land and land rights in rural areas in South Africa since 1994: focusing on the Vhembe district municipality - Ndou, Mulweliwanga (African Studies, 2025)
The paper investigates the progress that has been made when addressing women's access to land and land rights in the Vhembe District Municipality in Limpopo since 1994. Which allows us to critically analyze what changes have taken place in rural areas for the marginalized since the transition into democracy. As a member of the Vhembe community, I have great interest to see what democracy looks like for people who recognize both traditional leadership, which comes with customary law, and the constitution built on democracy. So, when we investigate how women interact in a community where both traditional leadership and constitutional government coexist. The paper then looks at how women negotiate the interests of the conflict between traditional leadership and constitutional government (local government). When speaking on traditional leadership, the paper has made it clear the role that traditional leaders played or should play in their community before, during and after the apartheid era. This also sees the need to look closely into what powers legislation has with the aim to ensure equality and equality in the Vhembe District Municipality for women who were seen to be marginalized and oppressed. Examining to what degree the latter is true in a state that has one of the most progressive constitution in the world. Some of these key pieces of legislations that are explored in the paper, are the Traditional Courts Bill and Communal Land Rights Act that addresses problems linked to power, land and gender in rural areas. However, overall through each legislation explored, one can see the lack of accountability on the part of traditional leaders. Much of what should be happening is not due to longevity of leaders who have been in power since 1994, and no desire to instill change that will bring on equality and equity for women and access to land because of what one describes as tradition, customs and values. However, one can see that the state recognizes the need for change as women in rural areas, especially the Vhembe District, rely on the land for their livelihood and development. As, women are taking up the responsibility as heads of households more and more, this has shown the state there needs to be progressive implementation of legislation. Thus, this paper finds that indeed women have been given rights to access land (on paper) in the area where traditional leaders still have a say however, this has also put women in a complicated position where they must speak up towards implementation of legislations. Even though one can argue that they are stuck between what customs and tradition says on the one hand, and what the law is saying about what role they should play in society on the other.